2018
DOI: 10.25014/revfacodont271.2018.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia a la flexión y módulo elástico de resinas de alta, mediana y baja densidad

Abstract: Aim: To determine the flexural strength and elastic modulus of high, medium and low density composite resins. Material and methods: 88 specimens of 25mmx2mmx2mm were divided into 11 groups of 8 according to the resin. Group 1: Filtek Z350 XT, ) and lower Wave Flow (2.17 +/-0.13) with significant differences (p<0,05). The time influenced significantly increasing values for both tests (p<0,05). Conclusion: Composite resins showed different behaviors. Time factor influenced increasing values excepting Rok and Fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies [4,[29][30][31][32] have assessed the flexural strength of direct-use resin composites following the guidelines of the International Organization for Standardization (ISO) 4049-2019 [23], which suggests a geometric dimension with a unit of analysis (resin bar) that does not adjust to the clinical reality; thus, this may generate some controversy in respect of results. Yap et al, concluded in their study that microflexural tests on resin composites gave higher values than flexural tests regardless of the conditioning medium, either air or artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [4,[29][30][31][32] have assessed the flexural strength of direct-use resin composites following the guidelines of the International Organization for Standardization (ISO) 4049-2019 [23], which suggests a geometric dimension with a unit of analysis (resin bar) that does not adjust to the clinical reality; thus, this may generate some controversy in respect of results. Yap et al, concluded in their study that microflexural tests on resin composites gave higher values than flexural tests regardless of the conditioning medium, either air or artificial saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the number of specimens prepared, although the minimum established is 5, in this case, 10 specimens of each material and each thickness were prepared in order to obtain greater precision in the study, as in Haselton et al [ 13 ] and Canals [ 11 ]. Other authors used eight specimens for each study group [ 20 ] or even twelve specimens [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the storage of the samples, this research chose to preserve them in artificial saliva at 37 ± 1 °C for 28 days. Authors such as Sezin M et al [ 20 ] also preserved their samples at the same temperature for 30 days. Ruttermann et al [ 21 ], Singh et al [ 17 ], and Poonacha et al [ 14 ] also opted for preservation of these in an aqueous or salivary medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation